2021
DOI: 10.3389/fgene.2021.678804
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Thermomorphogenesis-Related Genes for a Multi-Silique Trait in Brassica napus by Comparative Transcriptome Analysis

Abstract: In higher plants, the structure of a flower is precisely controlled by a series of genes. An aberrance flower results in abnormal fruit morphology. Previously, we reported multi-silique rapeseed (Brassica napus) line zws-ms. We identified two associated regions and investigated differentially expressed genes (DEGs); thus, some candidate genes underlying the multi-silique phenotype in warm area Xindu were selected. However, this phenotype was switched off by lower temperature, and the responsive genes, known as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The pattern of transcriptome variation between zws-ms and its NIL (zws-217), which produces normal siliques (i.e., single silique) grown under optimal conditions, unfolded in a colder environment 11 differentially expressed alternative splicing (DAS) genes, of which 4 were up-regulated and 7 were downregulated in a multi-silique line. Five such genes were associated with the multi-silique trait [188], and two thermos-morphogenesis genes switched off genes controlling the multi-silique trait in cold environments [189].…”
Section: Genomic Regions Regulating Splicing Of Quantitative Trait Lo...mentioning
confidence: 99%
“…The pattern of transcriptome variation between zws-ms and its NIL (zws-217), which produces normal siliques (i.e., single silique) grown under optimal conditions, unfolded in a colder environment 11 differentially expressed alternative splicing (DAS) genes, of which 4 were up-regulated and 7 were downregulated in a multi-silique line. Five such genes were associated with the multi-silique trait [188], and two thermos-morphogenesis genes switched off genes controlling the multi-silique trait in cold environments [189].…”
Section: Genomic Regions Regulating Splicing Of Quantitative Trait Lo...mentioning
confidence: 99%
“…As reported, silique number is crucial to seed yield per plant [2]. We previously reported zws-ms [3][4][5][6], a rapeseed material which had aberrant flowers with three pistils. Those abnormal flowers then developed into multi-silique trait, i.e., three independent siliques on one carpopodium.…”
Section: Introductionmentioning
confidence: 99%
“…In our earlier studies [3][4][5][6], we identified two associated regions for the multi-silique trait by using Whole Genome Re-sequencing (WGR) based on the construction of nearisogenic lines (NILs) zws-ms (multi-silique) and zws-217 (normal silique). Combined with transcriptome sequencing and gene annotation, some candidate genes were screened out.…”
Section: Introductionmentioning
confidence: 99%